2003
DOI: 10.1002/med.10054
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of urokinase‐type plasminogen activator receptor (uPAR) expression in cancer

Abstract: The involvement of the urokinase-type plasminogen activator (uPA) system in particular has been extensively studied in the pathogenesis of cancer. The molecular role of the uPA receptor (uPAR) is well characterized with its participation in cell migration and extracellular matrix (ECM) degradation. Over-expression of uPAR in cancer has been demonstrated in many studies and is considered an attractive target for anticancer agents. We and others have down-regulated uPAR expression in an attempt to inhibit cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
103
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(110 citation statements)
references
References 110 publications
6
103
1
Order By: Relevance
“…In addition, most malignant tumor cells already express high levels of uPAR (55). Thus, we sought to test the role of uPAR on the regulation of ␣5␤1/Fnmediated signaling in tumor cells expressing uPAR.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, most malignant tumor cells already express high levels of uPAR (55). Thus, we sought to test the role of uPAR on the regulation of ␣5␤1/Fnmediated signaling in tumor cells expressing uPAR.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, our results demonstrating considerably elevated PAI-1 and u-PAR expression under oxidative stress conditions indicate a necessity of control of the fibrinolytic system in these pathological states. High-plasma PAI-1 concentrations may lead to an increase in the deposition of fibrin and subsequent formation of a thrombus (Kohler and Grant 2000), whereas the u-PA and its receptor are known to be the agents participating in the pathogenesis of cancer (Alfano et al 2005;de Bock and Wang 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The uPA system consists of uPA, uPAR, plasminogen, and plasminogen activator inhibitor [18]. In vitro studies have shown that suPAR is associated with cell adhesion, migration, and proliferation [19,20].…”
Section: Discussionmentioning
confidence: 99%